Analysis of the economic factors determining the foreign direct investment inflows of Lithuania - Milena Seržantė; Benas Karalius (Trends Economics and Management, 2022)
Purpose of the article: This paper investigates the economic factors that impact Foreign Direct Investment (FDI) flows to Lithuania. The reason behind this is to find the economic factors that are significantly important for Lithuania's FDI attraction to ensure FDI stability and growth during economically challenging times.Methodology/methods: Analysis of scientific literature; data collection and systematisation; correlation analysis; and simple and multiple linear regressions.Scientific aim: First, literature analysis was used to find possible economic factors impacting the FDI that may be useful for Lithuania's case. This was followed by the identification of 5 main factors, namely inflation, unemployment, exchange rate, imports, and the GDP. The research led to statistical analysis, which revealed a strong correlation between the FDI and mentioned economic factors.Findings: The regression analysis answers the critical research question - the FDI flows to Lithuania are impacted by inflation, unemployment, and imports. The other two factors, namely the exchange rate and GDP, may be an underlying condition for attracting the FDI in other countries. It means that the previously mentioned three economic factors can or must be developed to attract investment to Lithuania.Conclusions: The results of multi-linear regression, revealing the Lithuanian FDI is impacted by inflation, unemployment, and imports, is suggesting an inference to develop or give an attention to those particular areas in order to attract the investments. The authors mentioned that inflation and unemployment could indicate uncertainty, therefore investors would look to these indicators to reason investment in a country, while imports were reasoned as a factor to think before investing due to the ability to measure market demand. Policymakers can use this paper to make the right decisions when tackling issues of foreign direct investment attraction.
Keywords: M15; M21; 650; FDI; Lithuanian economy; impact assessment; regression analysis